Identifying the educational needs of nurses caring for adults with congenital heart disease: A scoping review protocol - Tommy Lin; Monica Parry; Tieghan Killackey (PLoS ONE, 2026)
Objective The objective of this scoping review is to answer the question, “What is the existing evidence on nurses’ educational needs in caring for adults with congenital heart disease?” by identifying and summarizing research and grey literature on the educational needs of nurses who care for this population. Methods The scoping review will use the Joanna Briggs Institute (JBI) methodology and Preferred Reporting Items for Systematic and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) for reporting. Five databases will be searched: Medline, Embase, CINAHL, ERIC, and Scopus. Grey Matters, Google, and thesis and dissertation databases will be used to identify relevant grey literature. All types of published articles and non-empirical research will be included with no temporal, geographical, or language restrictions. Two independent reviewers will screen titles and abstracts, engage in full-text screening, and perform data extraction in Covidence. Any disagreements will be resolved through a third reviewer. Results The results of the scoping review will be analyzed using descriptive statistics and narrative analysis. The results will be reported using tables and figures. Findings will be disseminated through a manuscript and at conferences. Conclusion The findings of this scoping review aim to inform future research and interventions on the nursing care of adults with congenital heart disease. Registration The scoping review was registered on Open Science Framework ( https://osf.io/4t5hr ) on December 5, 2025.